The Model of Traditional Fisherman Empowerement at Buol Subdsitric, Biau, Buol Regency - Sudirman, Sudirman; Mamar, Sulaiman; Muhamad, Hasan; Rosmawati, Rosmawati; Yani, Ahmad (International Journal of English Literature and Social Sciences (IJELS), 2019)
The empowerment model has been increasingly known by the Indonesian people in the context of national development since the 1990s. This empowerment model is often considered as a manifestation of a community-centered development paradigm, because with this empowerment model, the community gets the highest possible chance to participate in development activities. The development approach using the empowerment model is a reaction from the previous development approach which tends to be growth-oriented and not on the aspect of equity. Nevertheless, this empowerment model has accelerated equity in development activities in our society. In Buol subdistrict since 2005, the empowerment model in community development has become one of the choices that is considered appropriate in answering the particular problems faced by traditional fishing communities in meeting the socio-economic needs of their family members. This study aimed to trace the model of empowering traditional fishermen to improve the welfare of family members. This study used a qualitative approach by determining the informants as many as 9 heads of traditional fishing families through a "purposive" technique with data collection techniques: (1). Observation of participants; (2). In-depth interview; (3). Focus Group Discussions (FGD). The results showed that the suitable empowerment models to improve the living welfare of traditional fishermen in Buol Village were a participatory model, collaborative model and partnership model, because in its implementation, the three empowerment models involved various elements including traditional fishing community members as empowered parties and all elements of the government , private sector and NGOs as empowering parties.